DIGITIZATION OF TOURIST ROUTES IN UKRAINE: CURRENT STATE AND DEVELOPMENT TRENDS (Development Service Industry Management, 2024)
The article analyzes the theoretical foundations of digitalization in the field of tourism. The concept of “digitalization of tourism”, its main concepts, and approaches to the digitalization of tourist routes are defined. The role of digital technologies in the development of tourism and the current state and development of tourism in Ukraine are analyzed. The current state and development trends of digitalization of tourist routes in Ukraine and the world, as well as existing digital technologies in the tourism industry of Ukraine and their development trends, are analyzed.Recommendations were made regarding measures to digitize tourist routes in Ukraine, in particular, regarding the development of an integrated digitization strategy for tourist organizations and branches of government in the field of tourism. According to the research results, a SWOT analysis of the current state of digitization of tourist routes in Ukraine was carried out and optimal digital solutions for specific tourist regions were proposed. It has been established that digitalization in tourism takes different forms and provides advantages for the state, region, individual enterprise, or consumer. At the same time, there are certain limiting factors for the use of digital technologies, the main of which are their high cost, no or weak Internet connection, imperfect legislation, lack of certain technologies, as well as state support for their implementation, and others. Disadvantages of digitization are that it can lead to unemployment (as human labor is replaced by technology), and there are also security issues (in particular, the risk of conducting transactions over the Internet).The current state and trends in the implementation of marketing campaigns for the promotion of digital routes are analyzed using the example of the Lviv region. It is justified that in the current conditions of the Russian-Ukrainian war and after our victory, Ukraine should make great efforts to support the digital development of tourism in the country, since these measures will attract more visitors, contribute to the creation of new jobs and economic development of the country.
Keywords: digitization; digital technologies; tourism; Ukraine